LOAD BALANCING MENGGUNAKAN METODE BUBBLE SORT PADA SISTEM DATABASE DENGAN MULTI SERVER - Prayitno Prayitno; Agus Basukesti; Yuliani Indrianingsih (Compiler, 2013)
The increasing demand for the utilize services computer networks has increased the traffic on the network. In general, the server provides service round the clock without a break, so that problems such as breakdown of communication in the network is lost that must be avoided. This cases need for a bettersystem with high performance and reliable every time. Current server technology development will be fast but the memory access speed is slower than the increase in the consumption of bandwidth. This is one o f the factors causing the bottleneck experienced of server. With the load balancing can be provide abetter solution. The concept used to provide a server has the same service. Then, the load balancing will check the CPU usage on each server. The server will perform selection based on the value of the smallest CPU Usage o f all existing servers. The application load balancing is placed before the user accessing ofserver with the object of distributing requests from the user to any of the servers that have been selected by the load balancer. Load balancing provides many benefits to systems that use it. The first, low cost, existing resources do not need to be replaced or discarded. Second, don't always need high end equipment. Third, easily developed when needed arose and a drastic decline in the quality o f service. Load balancing is also more secure, when a failure occurs on the server, load balancing application will redirect the user to the server is still available.